2015
DOI: 10.1111/chd.12252
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Atrioventricular Nodal Reentry Tachycardia Slow Pathways Using Voltage Mapping for Pediatric Catheter Ablation

Abstract: Visualization of the AV nodal slow pathway in a pediatric population is possible using voltage mapping technique with the potential to increase safety and efficacy. Variability exists in the voltage parameters needed to visualize individual slow pathways, which leads to a distinct learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…As with other studies, data from this study found that the atrial voltages were low at the successful ablation site. [2][3][4] Consistent with previous studies on AVNRT, as multiple wave fronts approach from different directions, it would be expected to cause a wide, fractionated, low-voltage electrogram. 5,6 Other studies have shown alterations in timing, electrogram amplitude, and His-bundle appearance in the perinodal area, depending on the fast-or slow-pathway conduction.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As with other studies, data from this study found that the atrial voltages were low at the successful ablation site. [2][3][4] Consistent with previous studies on AVNRT, as multiple wave fronts approach from different directions, it would be expected to cause a wide, fractionated, low-voltage electrogram. 5,6 Other studies have shown alterations in timing, electrogram amplitude, and His-bundle appearance in the perinodal area, depending on the fast-or slow-pathway conduction.…”
Section: Discussionsupporting
confidence: 79%
“…[2][3][4] In contrast to prior reports, which relied on the concept of the type I or type II voltage bridges as described by Bailin et al, in this study we considered a low-voltage area within the TK as a potential slow pathway, and we found low-voltage areas in all patients. 3 It should be noted that in an attempt to provide clean and accurate data, we were fairly rigorous about excluding patients with fewer than 30 voltage points in the TK, or those who have inadequate point density with which to evaluate propagation mapping.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We can speculate that a slightly higher RR of 10% in this study might be the consequence of the younger age and predominant RFA method of treatment. On the other hand, growing experience with cryoenergy [ 45 ], utilizing different ablation techniques [ 46 , 47 , 48 , 49 , 50 , 51 ], and utilizing 3D EAM systems has recently improved CRA outcomes, which are now similar to RFA outcomes [ 12 , 39 , 51 , 52 ]. A recent multicenter study experience from 12 centers (11 American) reported even better long-term results when using CRA in comparison to RFA [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that by using 3D electroanatomic mapping and a superimposed atrial electrogram voltage map, a low-voltage bridge in the KT can be visualized and used as a surrogate for the slow pathway ablation, and increase ablation accuracy and reduce recurrence rates. [15][16][17][18] Drago et al reported that by using voltage mapping of KT, combined with the search for the slow potential signal in 'low-voltage bridges' to guide cryoablation of AVNRT in children was very effective (with 100% success) in guiding cryoablation of AVNRT in pediatric patients. 19 We were not doing voltage mapping during this study period.…”
Section: Discussionmentioning
confidence: 99%